Ageing, cognitive disorders and professional practice. - O'Neill, Desmond; Reid, Alexander (My University, 2013)
Background: the workforce is ageing. The contribution of older workers is considerable. Their occupational health profiles differ from those of younger workers. Objective: we wished to establish whether consideration has been given by regulatory and professional bodies of the impact of ageing-related conditions such as dementia on professional practice. Methods: We e-mailed a questionnaire to 22 regulatory and professional bodies in the UK and the Republic of Ireland. We asked whether there are supports for their practitioners should they develop age-related diseases, (particularly cognitive disorders),whether the body considered that the practitioner was responsible for their own health, and whether the body has resources to arrange for medical review for their professionals if concerns arose regarding competence. Where bodies did not respond, information relating to the questions was extracted from their on-line resources. Results: thirteen bodies responded. None of these had specific supports to assist older workers. Some knew of other supports (occupational health, employee assistance supports, benevolent funds or counselling services). All of the bodies who responded either have or are developing structures to deal with concerns regarding their practitioners. Conclusion: The absence of specific policies for age-related diseases, (particularly dementia), among professional and regulatory bodies is a challenge for an ageing workforce in the liberal professions. Closer working between geriatric medicine, old age psychiatry, occupational health and professional bodies is recommended to develop age-attuned policies and systems which protect the public while supporting the professionals in both work and timely transition from work.
PUBLISHED
Keywords: older people; professional regulation; professional practice; occupational health; Alzheimer’s disease; dementia; Ageing; Neuroscience